O papel dos atributos morfofuncionais, fatores abióticos e bióticos na fenologia de Hirtella glandulosa Spreng. (Chrysobalanaceae) em floresta atlântica, na Chapada Diamantina, Brasil - Oliveira, Josevânia Carneiro de (2019)
We analyzed the roles of morphofunctional characters, abiotic and biotic factors on the phenology of Hirtella glandulosa Spreng. (Chrysobalanaceae) growing on contrasting soil types [latosol (clay rich) and lithosol (sandy) soils] in two Atlantic Forest sites in the Chapada Diamantina, northeastern Brazil. The text is divided into two chapters: the first considers leaf phenology and morphofunctional attributes, while the second examines the influences of abiotic factors, plant water status, and biotic factors of mutualistic (dispersal) and antagonistic (predation of pre-dispersal seeds) interactions on the phenological responses of H. glandulosa. Monthly data of the phenophases leaf fall, leaf flushing, budding, flowering, and immature and mature fruit production were collected among marked individuals in the following sites and periods: plateau/latosol site (2011, 2012, March/2018 to February/2019); river margin/lithosol site (2014, 2015, March/2018 to February/2019), through semiquantitative estimations of four classes (25% intervals). Five individuals per site were selected for evaluations of their morphofunctional characteristics in the dry and rainy seasons. During fruiting, frugivores/predispersal seed predators were observed. Fruits were collected for biometry and seed germination tests. Environmental data were collected to test their relationships with phenophases and morphofunctional characters. H. glandulosa was evergreen in both sites, with greater leaf fall and leaf flush intensity in the river margin/litholic site. Leaf traits, water potential and gas exchange differed between sites and between seasons. Reproductive phenology was seasonal at both study sites from March/2018 to February/2019. Comparing the time series for each site, there were no interannual variations of flowering and fruiting, with the exception of flowering in the upland site. Relative humidity influenced leaf flush and budding at both sites; the other phenophases were related to photoperiod. The fruits of the drupe type have a black epicarp and one seed per fruit within the pyrene. The seeds showed pre-dispersal predation by Coleoptera larvae that developed inside the seeds, leaving a small hole in the fruit. The birds Tangara cayana (male), Elaenia crustata and Tangara sayaca were observed feeding the fruits, being the last two considered potential dispersers. H. glandulosa presented similar rhythms of vegetative and reproductive phenology between sites, and demonstrated a functional and morphological variability of adaptive attributes that are crucial for its establishment and growth in sites with soil properties associated with different water availabilities. Reproductive patterns, with no significant variation between years at each site, seem to be adjusted for maintaining the supply of resources to favor interactions with predispersed seed predators and seed dispersers of the species.